NF-ĸΒ1 knockout reduces IL6 expression under hypoxia in renal cell carcinoma: NF-ĸΒ1 knockout reduces IL6 under hypoxia in RCC - S. Teixeira, Luiz Felipe; Bellini, Maria Helena (Cellular and Molecular Biology, 2023)
Renal cell carcinoma (RCC) is the most common adult renal epithelial cancer, accounting for more than 90% of all renal neoplasms. Clear cell RCC (ccRCC) is the most common subtype of RCC. Most patients with ccRCC have a mutation in the von Hippel-Lindau (VHL) tumor suppressor gene, which encodes a protein that downregulates various intracellular proteins, including hypoxia-inducible factor (HIF). Many molecules have been identified to be responsible for the aggressive phenotype of ccRCC, including the transcription factor nuclear factor kappa B (NF-кB). The increase in NF-кB activity observed in RCC is correlated with an increase in angiogenesis markers, such as interleukin 6 (IL-6). In recent years, several groups have demonstrated the functional role of NF-кB1 in RCC tumorigenicity. Herein, we used the CRISPR/Cas-9 technique to obtain an NF-кB1 knockout-human renal adenocarcinoma cell line. Expression of IL-6 at the mRNA and protein levels was analyzed under normoxia and hypoxia by real time-polymerase chain reaction and multiplex assay, respectively. The CRISPR/Cas9 technique was effective in producing 786-0 knockout cells for NF-κB1 (p105/p50), as confirmed by western blot analysis. Suppression of p50 expression in 786-0 single guide RNA (sg)1, 786-0 sg2 and 786-0 sg3 cells downregulated IL-6 mRNA and protein expression under normoxia and hypoxia. The observed decrease in the differential expression of IL-6 in hypoxia/normoxia is suggestive of a change in cellular responsiveness to hypoxia with respect to IL-6.